2006
DOI: 10.1016/j.memsci.2005.11.014
|View full text |Cite
|
Sign up to set email alerts
|

The influence of polarity on flux and rejection behaviour in solvent resistant nanofiltration—Experimental observations

Abstract: The separation characteristics of a dense polydimethylsiloxane (PDMS) membrane were studied using mixtures comprising xylene, cyclohexane or n-heptane with oxygenate components at concentrations up to 75%. The effects of polarity on flux and rejection performance were determined through a test matrix of solvent type, concentration, filtration pressure, crossflow rate and the degree of membrane crosslinking.In all cases involving alcohols, the more polar compound in the feed mixture was partially rejected by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 34 publications
(51 reference statements)
0
23
0
Order By: Relevance
“…Flux and steady state rejection are the principal measures and Figures 6-10 illustrate the salient features of swelling on these two parameters as well as representative swelling data for ethanol mixed with a second, lower polarity, solvent. For fuller descriptions the reader is directed to previous papers by the authors [11][12][13][14][15] where experimental arrangements and some of the data reported in Figures 6-10 are discussed in greater detail along with applications of nanofiltration models. All crossflow nanofiltration data reported in this paper were obtained with a DESAL membrane module (wetted surface area = 75 cm 2 ) at a crossflow rate of circa 1 l/min.…”
Section: Flux/rejection Performancementioning
confidence: 99%
“…Flux and steady state rejection are the principal measures and Figures 6-10 illustrate the salient features of swelling on these two parameters as well as representative swelling data for ethanol mixed with a second, lower polarity, solvent. For fuller descriptions the reader is directed to previous papers by the authors [11][12][13][14][15] where experimental arrangements and some of the data reported in Figures 6-10 are discussed in greater detail along with applications of nanofiltration models. All crossflow nanofiltration data reported in this paper were obtained with a DESAL membrane module (wetted surface area = 75 cm 2 ) at a crossflow rate of circa 1 l/min.…”
Section: Flux/rejection Performancementioning
confidence: 99%
“…The Hildebrand solubility descriptor is used in the model proposed by Bhanushali et al [7]. Other authors also report its possible importance for describing solvent-membrane affinity [3,5,6,8,39]. The results presented in Fig.…”
Section: Analysis Of the Descriptors Contribution To The Model Predicmentioning
confidence: 99%
“…However, some studies have shown that membrane swelling dramatically increased the flux of the solution without obvious changes in the solute rejection. 160 The difference may be caused by the difference of selective layer structure of the SRNF membranes. For the dense membranes, the free volume plays main role in rejecting of solutes, whereas the pores between the selective layer molecules determine the rejections to solutes for the porous membranes.…”
Section: The Crucial Factors Of Solute Transportmentioning
confidence: 99%